Goodnight moon - Brown, Margaret Wise, 1910-1952.; Hurd, Clement, 1908-1988 (London : Macmillan Children's Books, 2010)
A little bunny bids goodnight to all the objects in his room before falling asleep.
Keywords: Bedtime -- Fiction; Rabbits -- Fiction; Stories in rhyme